Pervious concrete as a sustainable solution for pavements in urban areas - Kováč, Marek; Sičáková, Alena (International Conference “Environmental Engineering”, 2017)
In the last few years, the use of pervious concrete as a pavement material in low-volume road applications (parking lots, residential roads, pedestrian zone or sidewalks) has gained importance due to its positive environmental aspects. Pervious concrete is one of the most promising sustainable material nowadays. It is a mixture of cement, coarse aggregate, water and admixture, while contains no or little amount of fine aggregates. Comparing a conventional concrete pavement, the pervious concrete system is designed to have enhanced amount of interconnected voids allowing water to percolate through the material. Population growth, continuing urbanization and the growth of impervious urban areas lead to specific environmental and societal impacts, especially urban heat island effect, risk of flash flood, worsening quality of water in river courses and so on. Pervious concrete has remarkable potential to counteract these adverse impacts while providing necessary structural integrity, thus supporting continued urbanization. Pervious concrete is currently under serious research and development in many countries because of enhanced interest of its properties. The paper is intended to bring comprehensive information on characterization, environmental benefits, performance issues and utilization possibilities of pervious concrete.
Keywords: characterization of pervious concrete; advantages and disadvantages of pervious concrete; performance issues of pervious concrete